PENELITIAN DAMPAK ROB TERHADAP PEMUKIMAN PENDUDUK DI SEMARANG - A Hamam (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2005)
The biggest quantity of water inundates Semarang coastel settlement in specific month every year. This research shows that the inundation is caused by the higher sea water level over the seashore, or by heavy rain falls at the hilly areas that add the land water quantity, which unable to flowing into the sea. This water then inundates the Semarang coastel. The variables used in the research area: geomorphology, the area inundatesd, land use, topography, physical aspects, and the tide. This research finds that the Semarang city's physical aspectneeds a more serious attention. In the long run, it is recommended to move some settlement affected the most by the inundation, and construct canal bank and city's administrator, it is suggested to watch the worsening environment and sanitation of the area inundated.